Rapid and efficient one-step generation of paired gRNA CRISPR-Cas9 libraries - Vidigal, Joana A. (Nat Commun, 2015)
The CRISPR-Cas9 system is a powerful tool to edit eukaryotic genomes that has recently been adapted for functional screens. Several of its applications—including the disruption of genes using Cas9-nickase and the generation of large deletions—require co-expression of two distinct guide RNAs (gRNAs). However, the lack of experimental approaches to generate pools of paired gRNA vectors prevents these applications from being scalable. Here we report a simple, inexpensive, one-step method that allows for the rapid and efficient cloning of gRNA pairs into expression vectors. We show that this method can be used to generate pooled libraries and is therefore suitable for in vivo and in vitro functional screens.